2010
DOI: 10.4028/www.scientific.net/amm.24-25.401
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bonded Splice Joints on the Flexural Response of Pultruded Fibre Reinforced Polymer Beams

Abstract: Abstract. Three Pultruded Fibre Reinforced Polymer (PFRP) 152 x 152 x 6.4mm Wide Flange (WF) beams were fabricated with a central two-plate splice joint. The 6.4mm thick PFRP splice plates were 210, 410 and 610mm long. Each beam was tested in symmetric four-point bending about its major and minor-axis and deflections, rotations and surface strains were recorded. Beam transverse stiffnesses, support rotations and splice rotational stiffnesses were quantified and compared with theoretical predictions. Predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…It was found that the predicted support rotations and mid-span deflections significantly under-estimated the values recorded in the four-point bending tests (counting from the left, see the last column in Table 8 and columns 5 and 7 in Table 9). This outcome was not altogether surprising, despite the fact that the Method of Transformed Sections combined with Moh -Area theorems had been shown to give reasonably accurate predictions for rotations and deflections of pultruded GFRP beams with mid-span bonded splice joints (see [10] and [11]).…”
Section: Comparison Of Analytical and Experimental Rotations And Deflmentioning
confidence: 99%
See 3 more Smart Citations
“…It was found that the predicted support rotations and mid-span deflections significantly under-estimated the values recorded in the four-point bending tests (counting from the left, see the last column in Table 8 and columns 5 and 7 in Table 9). This outcome was not altogether surprising, despite the fact that the Method of Transformed Sections combined with Moh -Area theorems had been shown to give reasonably accurate predictions for rotations and deflections of pultruded GFRP beams with mid-span bonded splice joints (see [10] and [11]).…”
Section: Comparison Of Analytical and Experimental Rotations And Deflmentioning
confidence: 99%
“…In [10] and [11] the first author used the Method of Transformed Section orems [17] to develop formulae for predicting the deformations of pultruded GFRP beams with bonded splice joints. He demonstrated that, in general, the formulae provided reasonably good predictions of the mid-span deflections and support rotations up to the serviceability deflection limit, though the rotational stiffnesses of the bonded splice joints were predicted with significantly lower accuracy.…”
Section: Analytical Predictions Of Transverse Deflections and Rotatiomentioning
confidence: 99%
See 2 more Smart Citations